KONTRIBUSI PENDIDIKAN ISLAM DALAM REPRODUKSI IDENTITAS SOSIAL MUSLIM INDONESIA - Saifudin Asrori; Ahmad Syauqi (Mimbar Agama Budaya, 2020)
Abstract. The Islamic education, Islamic boarding schools and madrasas, have made a very significant contribution to the implementation of education and social reform. Through the teaching process, in which the kyai as the main figure and the use of the ‘yellow book’, traditional Islamic ideas colored the early days of growing awareness as a nation and a State. When the New Order government carried out the development and modernization of society, there was a revival of a Muslim group called the “new middle class santri”, which took place in line with the modernization that occurred in the traditional Islamic educational institutions of the pesantren. Then in the era of democratization, the world of Islamic education experienced growth and development in various religious institutions and styles. Most of the pesantren are still committed to maintaining a moderate religious style, recognized as the foundation for the development of civil society and the formation of a ‘distinctive’, friendly, moderate, and tolerant social-political identity of Indonesian society. The Muslim character is different from other regions, especially the Middle East which is the axis of the Islamic world. However, a small proportion of pesantren are thought to promote the growth of religious chauvinism, teach a ‘narrow’ interpretation of Islam and provide a framework of thought and action in responding to socio-political change which often takes the form of a ‘jihad’. This article tries to explore the contribution of Islamic education to social change in the Indonesian Muslim community. Abstark. Dunia pendidikan Islam, pesantren dan madrasah, memberikan kontribusi sangat berarti dalam penyelenggaraan pendidikan dan reformasi kemasyarakatan. Melalui proses pengajaran, di mana kyai sebagai figur utama dan penggunaan ‘kitab kuning’, gagasan Islam tradisional mewarnai masa-masa awal tumbuhnya kesadaran sebagai bangsa dan Negara. Ketika pemerintah Orde Baru melakukan pembangunan dan modernisasi masyarakat, terjadi kebangkitan kelompok Muslim yang di sebut “kelas menengah santri baru”, berlangsung sejalan dengan modernisasi yang terjadi dalam lembaga pendidikan Islam tradisional pesantren. Kemudian pada era demokratisasi, dunia pendidikan Islam mengalami pertumbuhan dan perkembangan dalam beragam kelembagaan dan corak keagamaan. Sebagian besar pesantren masih tetap istiqomah dalam mempertahankan corak keagamaan yang moderat, diakui sebagai pondasi berkembangnya masyarakat sipil dan pembentukan identitas sosial-politik masyarakat Indonesia yang ‘khas’, ramah, moderat, dan toleran. Karakter Muslim yang berbeda dengan kawasan lainnya, khususnya Timur-Tengah yang merupakan poros dunia Islam. Namun ada sebagian kecil pesantren dianggap mendorong tumbuhnya chauvinisme keagamaan, mengajarkan penafsiran Islam yang ‘sempit’ dan memberikan kerangka pemikiran dan aksi dalam merespons perubahan sosial-politik yang seringkali berbentuk panggilan ‘jihad’. Artikel ini mencoba mengeksplorasi kontribusi pendidikan Islam dalam perubahan sosial masyarakat Muslim Indonesia.